ĐKXĐ : \(x\ne\pm2\)
PT \(\Leftrightarrow\dfrac{\left(x-2\right)^2-3\left(x+2\right)}{x^2-4}=\dfrac{2\left(x-11\right)}{x^2-4}\)
\(\Leftrightarrow\left(x-2\right)^2-3\left(x+2\right)=2\left(x-11\right)\)
\(\Leftrightarrow x^2-4x+4-3x-6=2x-22\)
\(\Leftrightarrow x^2-4x+4-3x-6-2x+22=0\)
\(\Leftrightarrow x^2-9x+20=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=4\\x=5\end{matrix}\right.\) ( TM )
Vậy ...
ĐKXĐ: \(x\notin\left\{2;-2\right\}\)
Ta có: \(\dfrac{x-2}{2+x}-\dfrac{3}{x-2}=\dfrac{2\left(x-11\right)}{x^2-4}\)
\(\Leftrightarrow\dfrac{\left(x-2\right)^2}{\left(x+2\right)\left(x-2\right)}-\dfrac{3\left(x+2\right)}{\left(x-2\right)\left(x+2\right)}=\dfrac{2\left(x-11\right)}{\left(x-2\right)\left(x+2\right)}\)
Suy ra: \(x^2-4x+4-3x-6=2x-22\)
\(\Leftrightarrow x^2-7x-2-2x+22=0\)
\(\Leftrightarrow x^2-9x+20=0\)
\(\Leftrightarrow x^2-4x-5x+20=0\)
\(\Leftrightarrow x\left(x-4\right)-5\left(x-4\right)=0\)
\(\Leftrightarrow\left(x-4\right)\left(x-5\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x-4=0\\x-5=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=4\left(nhận\right)\\x=5\left(nhận\right)\end{matrix}\right.\)
Vậy: S={4;5}